ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN BURNOUT SYNDROME PADA PEKERJA PT PP PRESISI PROYEK TOL CINERE-JAGORAWI SEKSI 3 TAHUN 2023 - Maulana Hazim Almagribi (2023)
Burnout syndrome, resulting from prolonged work-related stressors, significantly impacts employee productivity. This research investigates burnout syndrome factors in PT PP Presisi Cinere-Jagorawi Toll Project Section 3 employees. Employing a quantitative cross-sectional design, the study adopted total sampling technique, with 69 respondents from a population of 79. Data were collected by using Maslach Burnout Inventory, Multidimensional Scale of Perceived Social Support, and Work Locus of Control Scale questionnaires and then were analyzed by using the chi-square test. A univariate analysis indicates a 31.9% prevalence of burnout syndrome among employees. Bivariate analysis using chi-square reveals four significant factors: age (p=0.008), marital status (p=0.000), social support (p=0.000), and locus of control (p=0.000). The fostering of interpersonal connections through collaborative activities and the consideration of offering psychiatric services as needed are crucial for the company.